Manufacturing of selective electrode using modified graphite to determine silver ion in aqueous solution using Cyclic Voltammetry (CV) (Latakia University Journal -Basic Sciences Series, 2019)
This study investigated the manufacturing of a new electrochemical sensor (working electrode) to determine silver ions in aqueous solutions using Anodic Stripping Cyclic Voltammetry (ASCV), the electrode was prepared by mixing the graphite powder with effective material 1,3-diphenyl-5-P-nitrophenyl formazan, which was prepared and studied. The identity of the complex with the silver ion was proven using spectrophotometry in visible field and infrared IR spectroscopy. The optimal analytical conditions (electrolyte type and pH) and optimal technical conditions (accumulation potential and time, stripping potential and time) to determine silver ion in aqueous solutions using this sensor as working electrode, The results showed that the optimal analytical conditions were when using Sodium acetate - acetic acid as electrolyte where pH=5.6, and the optimal technical conditions were at accumulation potential and time Eacc= -400 mV, tacc= 80sec, stripping potential and time Estr = +300 mV, tstr = 100sec. The previous conditions were applied on a standard sample and gives ideal voltammetric curves Ep= +268mV, Ip= 23.86µA, the practical limit of detection was 0.100µg/l, the theoretical limit of detection was (L=2S) 0.080µg/l, retrieval coefficient was 100.5%, relative standard deviation 1.97%, Confidence range of 0.1004 ± 0.0497 within confidence level (95%), The results showed the validity of the modified electrode to act as a new working electrode and to increase the sensitivity of the analysis and its operation efficiently after comparing it with the unmodified graphite electrode.